DEVELOPMENT OF TEACHING MATERIALS FOR WRITING POETRY USING GOOGLE SITE FOR GRADE X HIGH SCHOOL STUDENTS - Novita Nupa; Widyatmike Gede Mulawarman; Jafar Haruna (Sean Institute, 2023)
This purpose of this research was to develop teaching materials, carry out learning, and describe the use of teaching materials for writing poetry through the Google Site media for class X SMA students. The Willis design R2D2 research model is used therein. The research model is intended to test the effectiveness of using a product and produce a product. The results of the development of teaching materials for writing poetry were validated by content or material experts with an average score of 93.26% and website-based electronic teaching materials experts with an average score of 90.62%, so that they can be used in implementation. to learn to write poetry. From the implementation of learning, an assessment of the learning plan was carried out by colleague 1 with an average score of 81.42% and colleague 2 with an average score of 83.57%. For the implementation of learning, an average score of 83.41% was obtained from colleague 1 and 82.91% from colleague 2. Small group trials were used to see the feasibility of website-based electronic teaching materials with an average score of 72.4 in the pretest and posttest. 85, and for pretest and posttest 74.6 for large group trials. Through the tests that have been carried out, it can be concluded that the use of the Google site is effective in helping students' poetry writing skills.